Pengaruh Dinamika Pendekatan Psikoanalisis Terhadap Kematangan Karir Pada Anak Berkebutuhan Khusus - Rendy Amora Jofipasi; Jon Efendi; Robbi Asri (Universitas Lancang Kuning, 2023)
This article discusses the exploration of psychoanalytic factors that affect career maturity in children with special needs. The research focuses on psychodynamic elements that may provide insight into career development in children with special needs. By analyzing subconscious conflict, psychosexual dynamics, and defence mechanisms, the study attempts to identify key factors that play a role in the formation of career maturity. Through the identification of these factors, it is expected to reveal a richer view of the impact of psychodynamics on professional maturity of children with special needs. The research seeks to provide a better understanding of the career path of children with special needs and integrate concepts of psychoanalysis. Hopefully the results can help design more appropriate and supportive intervention approaches to help them independence and social integration through career choices that fit their potential and specific needs. The results of this research can provide a deep understanding of how psychoanalytic factors contribute to career maturity in children with special needs, with the potential to provide guidance to support their professional development and facilitate their integration into society.